The Dilemma of Checks and Balances, Human Rights Protection, and Judicial Independence in Indonesia - Chinta Cintia; Rivan Padma Negara; Nisrina Faraas (Candidate: Jurnal Sains Politik, 2025)
The 1998 post-reform amendments to the 1945 Constitution marked a new era in the development of the rule of law in Indonesia, with an emphasis on the separation of powers, the protection of human rights, and the independence of the judiciary. However, more than two decades later, the implementation of this vision is still faced with various structural and practical challenges. This article critically evaluates the effectiveness of state institutional arrangements, particularly the trias politica, in maintaining checks and balances of power and accountability between the executive, legislative and judicial branches. In addition, it discusses the extent to which human rights guarantees explicitly stated in the constitution have been realized through laws and daily law enforcement, including the gap between ideal norms and field realities that often disadvantage vulnerable citizens. Finally, the article reveals the main obstacles in realizing the rule of law, such as political interference with the judiciary and the lack of autonomy of judges, which impede a fair and independent judiciary. Through an analysis of constitutional documents, empirical cases, and current literature, the study concludes that while the legal foundations are strong, systemic dilemmas such as institutional corruption and weak oversight are major impediments. Recommendations include further reforms to strengthen accountability mechanisms and public legal education, in order to realize a truly inclusive and sustainable rule of law.